2021
DOI: 10.5435/jaaos-d-20-00715
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Robot-assisted Total Hip Arthroplasty: Comparing Safety and Hospital Charges to Conventional Total Hip Arthroplasty

Abstract: Introduction: Utilization of robotic assistance is increasing for total hip arthroplasty (THA). However, few studies have directly examined the efficacy of this technique at reducing complications. This research aims to compare the rates of perioperative complications of robotic-assisted THA (RA-THA) with conventional THA (C-THA). Methods: This study screened more than 35 million hospital discharges between 2010 to 2014 using the National Inpatient Samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
(45 reference statements)
0
15
0
1
Order By: Relevance
“…For example, Kirchner et al. recently evaluated inpatient costs between RA‐THA and matched mTHA patients and found significantly higher average costs among the RA‐THA cohort ($20,046 vs. $18,258; p < 0.001) despite significantly lower length of stay (2.69 vs. 2.82; p < 0.001) 52 . Conversely, a Markov model analysis by Maldonado et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kirchner et al. recently evaluated inpatient costs between RA‐THA and matched mTHA patients and found significantly higher average costs among the RA‐THA cohort ($20,046 vs. $18,258; p < 0.001) despite significantly lower length of stay (2.69 vs. 2.82; p < 0.001) 52 . Conversely, a Markov model analysis by Maldonado et al.…”
Section: Discussionmentioning
confidence: 99%
“…recently demonstrated that RA‐THA was associated with a cost saving with an average differential of $1810 among private insurers and $945 for Medicare compared to manual THA 53 . As their analysis failed to consider the significant capital needed to purchase robotic systems, 52,54 centres with limited financial resources and case volume may not be able to implement related technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In the existing literature, the association between TA-THA and shorter LOS is unclear. Although several studies support this finding, 6,8,28,33 an NIS database analysis consisting of patients undergoing THA from 2005 to 2014 found no association. 16 In our analysis, patients in the TA-THA cohort were more likely to be discharged home as compared with the U-THA cohort, which is consistent with the prior literature.…”
Section: Discussionmentioning
confidence: 96%
“…Robotik kol yardımlı artroplastinin sorunlarından biri de konvansiyonel protez cerrahisine göre daha pahalı olmasıdır. Bu konuda yapılmış çalışmalar da [22] bunu göstermiş olup fiyat-etkinlik oranı açısından literatürde yapılmış kanıt düzeyi yüksek çalışma bulunmamaktadır. Ayrıca robotik cerrahide kemiklere 'array' adı verilen sensörler yerleştirilmekte olup ekstra kemik girişinin olması kırık ya da enfeksiyon açısından riskli olabileceği konusunda tartışmaya neden olmaktadır.…”
Section: Hasta Memnuniyetiunclassified